Recommendations for Framing Multi‐Stakeholder Tradespace Exploration. Issue 1 (13th September 2016) - Fitzgerald, Matthew E.; Ross, Adam M.
Abstract: Tradespace exploration is a rapidly advancing design and decision support paradigm that is particularly applicable to complex systems with many value‐driving dimensions. These systems commonly have multiple stakeholders that can exert critical influence on the system's conceptual design, necessitating the satisfaction of their needs, and often requiring negotiation. Previous research has suggested that classic tradespace exploration activities may reinforce negative negotiation behaviors through their framing of the multi‐stakeholder problem. This paper presents active research in recommendations for supporting inter‐stakeholder and stakeholder‐data interaction. These recommendations include the reframing of standard tradespace activities and visualizations using the combined insights of the negotiation, framing, and TSE literature and extend from problem formulation through exploration of the data.